STABILITY ANALYSIS OF A STOCHASTIC SIS MODEL WITH DOUBLE EPIDEMIC HYPOTHESIS AND SPECIFIC NONLINEAR INCIDENCE RATE. (2018) - KOUFI, AMINE EL; NAIM, MOUHCINE; BENNAR, ABDELKRIM; YOUSFI, NOURA
No abstract available